Diagnostic uncertainty in primary aldosteronism - Marković Bojan; Stojković Mirjana; Janić Tamara; Babić Jovana; Đurković Ivana; Joksimović Nata; Nedeljković-Beleslin Biljana; Ćirić Jasmina; Žarković Miloš (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor")
Aldosterone is a mineralocorticoid hormone originating from the glomerulosa zone of the adrenal cortex. Its main mechanism of action involves the reabsorption of sodium along with the secretion of potassium and hydrogen ions. It is the final hormonal signal in the renin-angiotensin-aldosterone system, which participates in the regulation of circulating volume and systemic vascular resistance. Hypokalemia and hypertension are key indicators for diagnosing hyperaldosteronism. We present the case of a patient who was diagnosed with hypertension at the age of 30. Hypokalemia was first recorded in his 59th year (2023) with a level of 3.1 mmol/L. The analyzed RAAS markers showed an elevated ALDO/ PRA ratio. Computed tomography revealed a change in the right adrenal gland, measuring 9 mm. Given that the baseline aldosterone values were within the normal range for the healthy population, with a suppressed renin activity peak in one sample, primary aldosteronism was suspected. Consequently, confirmatory suppression tests were required to establish the diagnosis.